Anteseden Loyalitas Nasabah : Islamic Branding, Kualitas Layanan dan Kepercayaan - Nugraha, Reno Iwan Candra; Solekah, Nihayatu Aslamatis (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2021)
The purphose of this study is to analyze the antecedents of customer loyalty of Bank BNI Syariah which is influenced by Islamic branding, service quality and trust. The sample in this study was 148 customers using purposive sampling using multiple regression analysis tools using SPSS 25. The results showed that Islamic branding, service quality and trust have an effect on customer loyalty. The implication of the results of this study is expected to maintain and improve the application of Islamic Branding and service quality, especially for PT. BNI Syariah KCP Jombang so as to gain customer trust that will foster a sense of customer loyalty